Effects of pre-exposure to hyperbaric hyperoxia on high-intensity exercise performance - Kawada, S.; Fukaya, K.; Ohtani, M.; Kobayashi, K.; Fukusaki, C. (The Journal of Strength and Conditioning Research, 2008)
This study comprised 2 main experiments: one was to determine the oxidative DNA damage under hyperbaric hyperoxia (HBO), and the other was to evaluate the effects of pre-exposure to HBO on high-intensity exercise performance. Healthy subjects (n = 8) inspired 100% O2 in an experimental chamber at a pressure of 1.3 atmospheres absolute (ATA) for 50 minutes once per week for 2 weeks. Urinary 8-hydroxy-2'-deoxyguanosine (8-OHdG) was measured as a marker of DNA oxidative damage on day 0 and on days 1, 3, and 5 after each HBO exposure. To investigate the effects of pre-exposure to HBO on high-intensity exercise performance, subjects (n = 6) performed maximal isometric knee extensor exercise (30 repetitions x 2 sets) with and without HBO pre-exposure (100% O2 at 1.3 ATA for 50 minutes). Urinary 8-OHdG did not show any significant change after HBO exposure. Isometric knee extensor torque was significantly lower during the first half of the first set of exercises after HBO pre-exposure compared with the normobaric normoxia (NBO) trial. The decreased torque was associated with the lower integrated electromyography with respect to time. Changes in the degree of ischemia-reperfusion in the vastus lateralis muscle during exercise were larger in the HBO pre-exposure trial than in the NBO trial. Muscle fatigue index, serum lactate concentration, heart rate, and systolic blood pressure showed no differences between the 2 trials. These results indicated that HBO exposure was harmless to DNA, and HBO pre-exposure did not enhance high-intensity exercise performance. As a practical application, athletes who require maximal muscle strength should not inspire high-concentration of O2 just before their competitions because it might, as the case may be, impair their performance.